AKTIVITAS DIURETIK KOMBINASI EKSTRAK BIJI PEPAYA (Carica papaya L) DAN BIJI SALAK (Salacca zalacca varietas zalacca (Gaert.)Voss) PADA TIKUS JANTAN GALUR WISTAR (Rattus norvegicus L) - Nurihardiyanti Nurihardiyanti; Yuliet Yuliet; Ihwan Ihwan (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Research on diuretic activity of seed extract combination of papaya (Carica papaya L) and snake fruit (Salacca zalacca (Gaert.) Voss) to male wistar strain rats (Rattus norvegicus L.) has been conducted. This study aimed to determine the diuretic effect of the seed extract combination and its effective dose combination as diuretics. The extract was prepared by maceration method using ethanol 96%. Diuretic activity test was divided into 5 treatment groups. Each group consisted of 5 rats. Group 1 (negative control) was given suspension of Na-CMC 0.5%; Group 2 (positive control) was given furosemide 3.6 mg/kgBW; Group 3, 4, and 5 were given dose combination of snake fruit seed extract and papaya seed extract successively at “37.5 mg/kgBW + 7.5 mg/kgBW”; “70 mg/kgBW + 15mg/kgBW”; and “140 mg/kgBW + 30 mg/kgBW”. Each rat was then orally given warm distilled water (70°C) 10ml/100gBW as loading dose. The excreted urine volume was measured and recorded every 30 minutes for 6 hours which was continued to cumulative urine volume calculation. Furthermore, sample was taken from the cumulative urine to measure levels of sodium (Na), potassium (K), and the pH of the urine. Data were statistically analyzed using ANOVA (Analysis of Variance). The results showed that the effective extract dose combination was found in Group 5’s dose (140 mg/kgBW of snake fruit seed extract and 30 mg/kgBW papaya seed extract) with diuretic activity index of 1.48; urine pH of 7.52; sodium saluretic index of 1.62; and potassium saluretik index of 1.56